Constructing a Railway Viaduct Crossing KL - Kuala Selangor Expressway (LATAR) for ECRL Project: Technical Feasibility and Challenges - Bin Asmadi, Daniel Saputra (Progress in Engineering Application and Technology, 2025)
This study investigates the technical feasibility and engineering challenges in constructing a railway viaduct crossing the KL-Kuala Selangor Expressway (LATAR) at Bridge 18, as part of the East Coast Rail Link (ECRL) alignment. A mixed-methods approach was applied, combining qualitative interviews and focus group discussions with field measurements and technical data analysis. Key challenges include limited construction space, soil instability, and minimum clearance requirements above the expressway. Findings indicate that a special span using a Segmental Box Girder (SBG) with full-span launching and bored pile foundations is the most viable solution. The study offers practical references for future viaduct construction projects in similarly constrained locations in Malaysia.